2002
DOI: 10.1056/nejmoa013171
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone in Children with Autism and Serious Behavioral Problems

Abstract: Risperidone was effective and well tolerated for the treatment of tantrums, aggression, or self-injurious behavior in children with autistic disorder. The short period of this trial limits inferences about adverse effects such as tardive dyskinesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
604
2
13

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,318 publications
(648 citation statements)
references
References 23 publications
29
604
2
13
Order By: Relevance
“…Although both are approved for the treatment of irritability, an associated ASD symptom, both have shown efficacy in reducing core symptoms as well. Specifically, randomized controlled trials of risperidone in individuals with ASD found significant reductions in challenging behaviors, such as irritability and hyperactivity [596-600], and significant improvement in core autism symptoms [601-604]. Randomized controlled trials of aripiprazole have also found a decrease in irritability and hyperactivity and decreased instances of repetitive behaviors in children with ASD over the course of treatment [604,605].…”
Section: Reviewmentioning
confidence: 99%
“…Although both are approved for the treatment of irritability, an associated ASD symptom, both have shown efficacy in reducing core symptoms as well. Specifically, randomized controlled trials of risperidone in individuals with ASD found significant reductions in challenging behaviors, such as irritability and hyperactivity [596-600], and significant improvement in core autism symptoms [601-604]. Randomized controlled trials of aripiprazole have also found a decrease in irritability and hyperactivity and decreased instances of repetitive behaviors in children with ASD over the course of treatment [604,605].…”
Section: Reviewmentioning
confidence: 99%
“…1 According to a recent survey, 31% of children with autism spectrum disorders take an antipsychotic medication, 2 with risperidone one of the most popular atypical antipsychotics prescribed. Several open trials of risperidone in autism (reviewed in 3,4 ) and three placebo double-blind randomized controlled trials, [5][6][7] reported significant improvements in at least half of the patients evaluated. 4,8 Risperidone was shown to be well tolerated and effective in treating aggressiveness, hyperactivity, irritability, self-injurious behaviours, stereotipies, social withdrawal and lack of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The approval was largely based on the findings from two randomized, controlled trials in 79 and 101 children with autistic disorder and severe behavioral problems. 4,5 In the larger study, children in the risperidone group had a 57% reduction in irritability compared to only a 14% reduction among children in the placebo group (p Ͻ 0.001). 4 A second atypical antipsychotic, aripiprazole, was approved in late 2009 for the same indication (irritability) in children with ASD, based on the results from two 8-week randomized, placebo-controlled trials in 98 and 218 patients.…”
Section: Introductionmentioning
confidence: 86%
“…4,5 In the larger study, children in the risperidone group had a 57% reduction in irritability compared to only a 14% reduction among children in the placebo group (p Ͻ 0.001). 4 A second atypical antipsychotic, aripiprazole, was approved in late 2009 for the same indication (irritability) in children with ASD, based on the results from two 8-week randomized, placebo-controlled trials in 98 and 218 patients. 6,7 In the larger study, irritability improved 14% to 21% over 8 weeks, but side effects, including sedation, tremor, drooling, and weight gain, were common.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation